2018
DOI: 10.1016/j.jpor.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Development, validity and reliability of the Orofacial Esthetic Scale — Spanish version

Abstract: OES is a valuable instrument to measure the orofacial appearance construct for Spanish-speaking populations. OES was concluded to be unidimensional with excellent score reliability and sufficient convergent score validity when compared with other Orofacial Appearance measures. Our results suggest that OES could be used in Spanish-speaking patients, an important and growing population around the globe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…It was necessary to allow for a correlation between the errors of items 1 ("facial appearance") and 2 ("facial profile appearance") to obtain an adequate fit of the factorial model to the data. Thus, unidimensionality of OES was confirmed, consistent with what was observed in other versions of this instrument (Bimbashi et al, 2015;John et al, 2012;Larsson et al, 2010;Reissmann et al, 2015Reissmann et al, , 2019Zhao & He, 2013). Although John et al (2012) pointed to a plausible theory that OA assessed by OES has two factors, the authors recommend that the one-dimensional proposal should be the choice because they report that the presence of two distinct aspects does not contribute to improving the estimate of the OA concept.…”
Section: Subsamplesupporting
confidence: 80%
See 3 more Smart Citations
“…It was necessary to allow for a correlation between the errors of items 1 ("facial appearance") and 2 ("facial profile appearance") to obtain an adequate fit of the factorial model to the data. Thus, unidimensionality of OES was confirmed, consistent with what was observed in other versions of this instrument (Bimbashi et al, 2015;John et al, 2012;Larsson et al, 2010;Reissmann et al, 2015Reissmann et al, , 2019Zhao & He, 2013). Although John et al (2012) pointed to a plausible theory that OA assessed by OES has two factors, the authors recommend that the one-dimensional proposal should be the choice because they report that the presence of two distinct aspects does not contribute to improving the estimate of the OA concept.…”
Section: Subsamplesupporting
confidence: 80%
“…The adequate validity (construct, convergent and concurrent) and reliability of OES-Pt observed in different subsamples strengthens the use of the instrument to obtain more accurate evidence related to OA in this population. The instrument has been successfully implemented in other cultures/countries as well (Bimbashi et al, 2015;John et al, 2012;Larsson et al, 2010;Reissmann et al, 2015Reissmann et al, , 2019Zhao & He, 2013), indicating this is a robust instrument.…”
Section: Subsamplementioning
confidence: 96%
See 2 more Smart Citations
“…The OES instead evaluates the overall satisfaction of the patient with his/her esthetic appearance. As the most common instrument used in research, the OES has good psychometric properties and has been adapted cross-culturally to several languages such as; Croatia,Chinese,Albanian,Dutch,Germany,Arabic,and Spanish [25,29,[32][33][34]37,40,41]. Although the instrument developed by Tortopidis et al showed good reliability, there has been no report of its use in other published studies.…”
Section: Discussionmentioning
confidence: 99%